Bhutan Urban Policy Notes : Regional Development and Economic Transformation - World Bank (World Bank, Washington, DC, 2019)
This paper is part of a series of four Urban Policy Notes that provide a critical review on emergent challenges to Bhutan’s increasing urbanization and its ramifications for growth, livability and sustainability in line with the directives of the 12th Plan and Vision 2020. The four notes are: (a) Regional Development, (b) Municipal Governance and Finance, (c) Affordable Housing and (d) Urban Resilience. These notes build on the long engagement between the Royal Government of Bhutan (RGoB) and the World Bank on urban issues as well as the experiences of urban operations under Bhutan Urban Development Projects I (1999-2006) and II (2010-2019) and intend to support the RGoB on key and emerging urban topics and guide Bank’s future analytical and investment support in the urban sector. This Policy Note aims to present critical policy options for leveraging urbanization and supporting regional development to enable Bhutan to achieve sustainable growth, spur private sector development job creation and support balanced spatial development. The Note (a) takes stock of recent trends in urbanization, economic growth, and demographic change from a spatial perspective, (b) suggests a framework to guide policy making and (c) better target investments to leverage the potential of urban areas for job creation and livability, while also addressing the needs of poorer small towns and less populated rural areas. These focused areas align with the RGoB's overall goal of balanced and equitable development.